IMPLEMENTASI KONSEP PENDIDIKAN K.H. IMAM ZARKASYI DI PONDOK PESANTREN DARUSSALAM BOGOR - Nur Apriani; Fuad Ahmad Riva'i; Milahtul Latifah (Institut Ummul Quro Al-Islami Bogor, 2023)
Islamic education has given the biggest contribution to the almost of institutions, include of it is pesantren. Pesantren is the central of dakwah for creating umat’s cadre. This study examines the K.H. Imam Zarkasyi’s education concept and its implementation in Darussalam Bogor Islamic boarding school. To achieve these aims, analytic descriptive research was carried out, both by interview and observation. With this metodh found that Imam Zarkasyi’s concept of education was Islamic Teachers Training College (ITTC) with direct method that purpose the Islamic, knowledge, and civil orientation. The teacher’s qualification was paid attention to the quality and the social skills. The students, with boarding system are learning languages, islamic, and universes studys. Learning media focus on teaching aids. The community environment was heterogeneous, and the evaluation system was structured and tiered. The education system in Darussalam Bogor boarding school has the similarity with Imam Zarkasyi’s with some additional in education aims that seeking knowledge is worship in order the graduation has strong desire to continue his study to the higher. On the side of subject, the students study the Islamic classic book, recite shalawat, and ratib. Besides that, the teachers didn’t able to fully imitate. In management evaluation aspect didn’t able to evaluate the attitudes and ways of thinking